The relative withdrawal of GFAP—An essential component of brain evolution - Kálmán, Mihály (Frontiers in Neuroanatomy, 2025)
The glial fibrillary acidic protein (GFAP) is the principal intermediate filament protein and histochemical marker for astroglia. It appears contradictory that there are extended GFAP-poor or even GFAP-free areas in the brains of various vertebrate clades: cartilaginous and ray-finned fishes, and amniotes. The “Relevant Subsections: Extended GFAP-free areas in various vertebrates” section in this study reviews our GFAP mapping studies on the brains of 58 species within these clades, as well as mappings from other authors, and demonstrates that these areas appeared independently from one another in the more advanced groups of different clades; it raises the supposition that the lack of GFAP is an apomorphic phenomenon. The GFAP expression has withdrawn mainly relatively: the GFAP-immunonegative areas increased more than the immunopositive ones. Primarily, regions that expanded and increased in complexity during evolution lack GFAP immunopositivity (except for their perivascular glia). The absence of GFAP expression, however, does not indicate the lack of astroglia. In the areas immunonegative to GFAP, astrocytes were visualized using other markers, such as glutamine synthetase or S-100 protein. In birds and mammals, lesions induced GFAP expression in these areas. It shows that the ability to express GFAP is not lost but has become facultative. These data suggest that the lack of GFAP production may provide an evolutionary advantage. The “Discussion” section relates the GFAP “withdrawal” to other steps of evolution: the increasing complexity and thickening of the brain wall, as well as the appearance of the astrocytes, particularly protoplasmic astrocytes, and then examines the proposed evolutionary advantages and disadvantages of the absence of GFAP. The role of the relative “withdrawal” of GFAP expression in brain evolution remains to be definitively answered. The most probable candidates may include the absence of synthesizing an unnecessary protein, improved adaptation of astrocytes to the demands of neurons, and an increased capacity for synaptic plasticity. In contrast, one must consider that the withdrawal of GFAP may not be a primary phenomenon but rather a consequence of the evolution of neural networks.